2016
DOI: 10.1071/an14012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy of a topical anaesthetic formulation and ketoprofen, alone and in combination, on the pain sensitivity of dehorning wounds in Holstein-Friesian calves

Abstract: The aim of this study was to investigate the effect of a topically applied local anaesthetic and the non-steroidal anti-inflammatory drug ketoprofen, alone and in combination, on the pain sensitivity response of calves to dehorning (mean age 2.2 months). Calves were randomly allocated and blocked by age to one of four groups. Groups were: scoop dehorning (D, n = 8), scoop dehorning + i.m. administration of 3 mg/kg ketoprofen (DK, n = 8), scoop dehorning + application of topical anaesthetic (DTA, n = 7) and sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Scoop dehorning in younger calves typically creates bony wounds of small surface area, with haemorrhage, which may limit the quantity of TA absorption. Haemorrhage reduces the ability of the TA to adhere and remain on the wound and has been observed previously [23]. The lack of epithelial or mucosal tissue on small bony dehorning wounds means there is minimal surface area for effective TA absorption, with most nociceptors likely located in the wound edges.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Scoop dehorning in younger calves typically creates bony wounds of small surface area, with haemorrhage, which may limit the quantity of TA absorption. Haemorrhage reduces the ability of the TA to adhere and remain on the wound and has been observed previously [23]. The lack of epithelial or mucosal tissue on small bony dehorning wounds means there is minimal surface area for effective TA absorption, with most nociceptors likely located in the wound edges.…”
Section: Discussionmentioning
confidence: 83%
“…Topical local anaesthetics are applied to the skin surface (less absorption) or directly onto the mucosal tissue or open wound to induce rapid and lasting local anaesthesia [20,21]. We have previously reported on a topical anaesthetic wound dressing formulation reducing short-term pain sensitivity and increasing mechanical nociceptive thresholds following scoop dehorning in calves [22,23]. This multipurpose formulation contains lignocaine and bupivacaine for local anaesthesia, cetrimide for antisepsis, and aluminium chlorohydrate for astringency of the wound (modified from Tri-Solfen ® ; Bayer Animal Health, Pymble, NSW, Australia).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the efficacy of a topical anaesthetic formulation (Tri-Solfen®, Bayer Animal Health, Pymble NSW Australia) for use during mulesing [ 14 ], tail docking and surgical castration [ 15 ] in lambs and surgical castration in beef calves [ 16 ]. Preliminary studies have shown that modified formulations of Tri-Solfen® applied to dairy calves during scoop dehorning significantly reduced the sensitivity of wounds up to 1.5 h [ 17 ] and 5 h [ 18 ] following the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The overall aim of the previous studies [ 17 , 18 ] and the current study, are to investigate options for providing pain relief to calves undergoing scoop dehorning that are both effective and practical to use on-farm.…”
Section: Introductionmentioning
confidence: 99%